2022
DOI: 10.1113/jp282000
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term exercise‐induced protection of cardiovascular function and health: why and how fast does the heart benefit from exercise?

Abstract: Regular exercise training has potent and powerful protective effects against the development of cardiovascular disease. These cardioprotective effects of regular exercise training are partly explained through the effects of exercise on traditional cardiovascular risk factors and improvement in cardiac and vascular health, which take several weeks to months to develop. This review focuses on the observation that single bouts of exercise may also possess an underrecognized, clinically useful form of immediate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 95 publications
2
13
0
Order By: Relevance
“…Thus, there may be further clinical benefit by administering multiple bouts of RIPC (Table 2). The pattern and underlying mechanisms of cardiovascular protection with repeated RIPC may be similar to that observed after short-term aerobic exercise (Thijssen et al, 2018;Thijssen et al, 2022). In heart failure patients, 1 week of RIPC increased coronary artery flow reserve by ∼20% (Kono et al, 2014).…”
Section: Potential Mechanisms Of Single Bout Ripc On Vascular Functio...mentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, there may be further clinical benefit by administering multiple bouts of RIPC (Table 2). The pattern and underlying mechanisms of cardiovascular protection with repeated RIPC may be similar to that observed after short-term aerobic exercise (Thijssen et al, 2018;Thijssen et al, 2022). In heart failure patients, 1 week of RIPC increased coronary artery flow reserve by ∼20% (Kono et al, 2014).…”
Section: Potential Mechanisms Of Single Bout Ripc On Vascular Functio...mentioning
confidence: 84%
“…Lastly, considering the ischaemia and reperfusion experienced during exercise, aerobic fitness or prior physical activity may alter the efficacy of RIPC. This topic regarding the potentially additive or overlapping adaptations of exercise and RIPC is effectively addressed in recent review papers (Thijssen et al, 2018(Thijssen et al, , 2022. Collectively, multiple factors have been identified that potentially affect the clinical use and efficacy of RIPC.…”
Section: From Animal Model To Human Clinical Research Modelmentioning
confidence: 99%
“…The main originality of our work was to evaluate the effects of a widely recognized cardiovascular protective strategy on the exacerbation of HG-induced I/R injury on the vasculature. Among protective strategies, a large number of studies have been able to demonstrate positive effects of exercise on vascular function [ 16 , 39 ]. More specifically, exercise training was proven to be able to limit endothelial vulnerability to I/R in both human [ 16 , 17 ] and rodent models [ 18 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is widely recognized as a health maintenance method and it has numerous benefits ( 19 , 20 ). It is acknowledged that exercise may accelerate metabolism, build cardiorespiratory capacity, improve immunity, and relieve mental stress ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%